Analysis of compatibility of tornado material with physics material of grade xii senior high school - Kurnia Andini; Ahmad Fauzi (ASEAN Natural Disaster Mitigation and Education Journal, 2023)
One way to increase disaster knowledge is integrate disaster material into physics learning in schools. For tornado material to be easily raised in the physics learning process, learning resources are needed such as physics textbooks that are integrated with tornado material. However, not all physics materials can be integrated with tornado materials. So, it is necessary to first analyse the level of compatibility of tornado materials with physics materials in senior high school. This research is descriptive research with a qualitative approach. Research data is primary data collected through documentation studies. The primary tool used in this research is an analysis table of the compatibility of tornado material with physical material. The result of this research is the compatibility of tornado material with Senior High School physics learning material class XII semester 1 with a value of 0.316 and class XII semester 2 with a value of 0.348. In class XII semester 1, only 1 of 5 subject matter has compatibility to be integrated with tornado material, namely static electricity material with a compatibility value of 0.58. In class XII semester 2, there are 2 out of 6 subject materials that have a compatibility to be integrated with tornado material, namely electromagnetic radiation, and technology material with a compatibility value of 0,67 and 0,42. The research’s finding is that physics material for class XII in semesters 1 and 2 is less compatible for integration with tornado material.